National archives of Malaysia, Melaka / Nor Azimah Zulkifli - Zulkifli, Nor Azimah (Bachelor in Science (HONS) Records Management, 2015)
Records management is a key driver of operational efficiency and offers significant business benefits. Implementing an effective records management program creates more value from a company's information assets while mitigating the risks associated with litigation, audit, and disaster. Good records management will ensure all the records will be keep and protect safely. To ensure all the records will be keep safely, it is important to make sure the place to keep all those records is secure. For example, National Archives of Malaysia, Melaka as a place to keep, and protect the historical and valuable record. The records need the special treatment. To ensure all the records free from insects, metal, and others, records need to make cleaning process. There is workflow on how to handling and managing the records starting from receiving records from the government departments until the process of keeping and placing on the shelves. After 25 years old, the records can be access by the researchers and public. Not just focusing to the records management, but also in handling and managing office management. At the same time, focus in special project which "Determining Departmental Records Officer (PRJ) and Departmental Records Administrative Assistant (PTRJ) in Government Departments in Negeri Melaka." And also find the limitation of the National Archives of Malaysia, Melaka and give the solution towards those problems. Keywords: Records management, National Archives of Malaysia, Melaka, office management, Departmental Records Officer (PRJ), Departmental Records Administrative Assistant (PTRJ)